2012
DOI: 10.1002/cncy.21255
|View full text |Cite
|
Sign up to set email alerts
|

The Johns Hopkins Hospital template for urologic cytology samples

Abstract: BACKGROUND: The most important indicator for urologic surgeons at The Johns Hopkins Hospital to have a patient undergo cystoscopy is a cytologic diagnosis of high‐grade urothelial carcinoma. The template was designed to standardize diagnostic categories so clinicians can manage their patients uniformly. The template was based in part on the Bethesda System for cervical cytology. METHODS: According to the template, reactive/inflammatory changes were included in the negative group (no urothelial atypia or malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 13 publications
7
88
0
4
Order By: Relevance
“…Among those features, hyperchromasia has consistently been shown to be an independent predictor of HGUCA; however, because it has also been frequently reported in LGUCA, it makes it an essential but nondiscriminatory feature between low-grade and high-grade urothelial lesions. 6,[8][9][10][11][12] Similarly, irregular nuclear membranes, although most often reported in specimens harboring HGUCA, can also be present in LGUCA and even in certain reactive conditions, in particular stone atypia. 4,5,9 At least 3 studies, including the current one, have reported a significant association between pleomorphism and subsequent HGUCA, making it a powerful feature in assessing urine cytology specimens and in differentiating low-grade from high-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Among those features, hyperchromasia has consistently been shown to be an independent predictor of HGUCA; however, because it has also been frequently reported in LGUCA, it makes it an essential but nondiscriminatory feature between low-grade and high-grade urothelial lesions. 6,[8][9][10][11][12] Similarly, irregular nuclear membranes, although most often reported in specimens harboring HGUCA, can also be present in LGUCA and even in certain reactive conditions, in particular stone atypia. 4,5,9 At least 3 studies, including the current one, have reported a significant association between pleomorphism and subsequent HGUCA, making it a powerful feature in assessing urine cytology specimens and in differentiating low-grade from high-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…4 ), the long debated category by different authors [2][3][4][5][6][7][8][9] . In fact, our study showed Values are expressed as n (%).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnoses were made using the Johns Hopkins Template for Reporting Urinary Tract Cytology (JHHT) because the Paris System for Reporting Urinary Tract Cytology had not yet been established at JHH during this study period [20-22]. The JHHT utilized a malignant category, “high-grade urothelial carcinoma” (HGUC), a benign category, “no urothelial atypia or malignancy” (NUAM), a low-risk indeterminate category, “atypical urothelial cells of undetermined significance” (AUC-US), and a high-risk indeterminate category, “atypical urothelial cells, cannot exclude HGUC” (AUC-H).…”
Section: Methodsmentioning
confidence: 99%